European strategy for confronting crises (قضايا سياسية, 2024)
Within the framework of an international system filled with events, variables, and crises that leave their impact on all its components, the crises that obstructed the course of the European Union’s work were numerous and varied, ranging from direct crises within the European scope to external, regional and international crises. These crises posed challenges to European unity, so the European Union was present and aware to these variables and crises and their effects and the necessity of confronting them through a unified European strategy that can deal with, manage, adapt to, or find solutions to these crises through procedures, policies, aid packages, and strategies for each field. However, all of these European strategies to confront crises are not at the required level which puts and develops radical solutions to these crises. The European responses, represented by the strategies to confront the crises, were varied. Some of them were successful and influential, albeit in a relative manner, they expressed relative European consensus in some crises and contributed to some extent to the possibility of dealing with the crises, while others failed in the face of other crises. The European strategies for dealing with crises were timid and modest strategies and did not always express the collective and unified European opinion. The influences and variables that were embodied in the form of crises were stronger than the European will to confront them, this was also affected by the prioritization of the national and private interests of the European countries over the collective and unitary interests and the international pressures and influences that affected them. It leads to influencing European strategies and their effectiveness, all of which has implications for the status, strength and effectiveness of the European Union at the international level. Accordingly, the European Union needs stronger, more integrated and consensual positions and strategies among member states that express a unified European role and influence, enhance its international standing, and parallel the success it has achieved throughout the stages it has gone through.